Returns to International Migration: Evidence from a Bangladesh-Malaysia Visa Lottery - Ahmed Mushfiq Mobarak; Iffath Sharif; Maheshwor Shrestha (Institute of Labor Economics (IZA), 2021)
We follow 3,512 (of 1.4 million) applicants to a government lottery that randomly allocated visas to Bangladeshis for low-skilled, temporary labor contracts in Malaysia. Most lottery winners migrate, and their remittance substantially raises their family's standard of living in Bangladesh. The migrant's absence pauses demographic changes (marriage, childbirth, household formation), and shifts decision-making power towards females. Migration removes enterprising individuals, lowering household entrepreneurship, but does not crowd out other family members' labor supply. One group of applicants were offered deferred migration that never materialized. Improved migration prospects induce pre-migration investments in skills that generate no returns in the domestic market.
Keywords: F22; O12; O15; 330; government-intermediated international migration